â€œFrom the Series, I See that LGBTQ+ Characters are Ordinary Peopleâ€: An Audience Study on Netflix Series with LGBTQ+ Themes in 2020â€“2022 - Trisnawati, Ririn Kurnia; Sari, Tribuana; Hadiningrum, Indriyati (Bina Nusantara University, 2023)
The research focused on how the audience of gender-diverse series in Indonesia reacted to the LGBTQ+ themes broadcasted in some Netflix series aired from 2020 to 2022. It was interesting to discuss, considering that LGBTQ+ issues were still taboo, and that Indonesian society was known to be conventional and religious. By examining the audienceâ€™s reactions to the narration of LGBTQ+ themes, the research delved deeper into how Indonesian audience members problematize the LGBTQ+ issues in the Netflix series. The research was conducted with the qualitative research method by asking 70 participants, from whom validated informed consent was retrieved in advance, to answer the questions posed in the online questionnaire employed herein and by inviting them to join Zoom-mediated interviews. Three problematizations are found: Netflixâ€™s ideology related to its LGBTQ+ content, audience perception about the LGBTQ+ community, and audience religiosity before and after watching such a series. There are also varying views on these problematizations according to the various manners in which audience members are reasoning, which are subsequently assigned to several clusters. Ultimately, such problematizations help shed light on how Netflix and its LGBTQ+ content is dynamically perceived by the audience.Â